Strategi Public Relations PT. Pos Indonesia (Persero) dalam Mempertahankan Reputasi di Era Digital: Studi Kasus PT. Pos Indonesia - Arsya Elan Bramantya; M.E. Fuady (UNISBA Press, 2023)
Abstract. Human civilization has experienced a very long journey along with the development of the cognitive abilities of the human race from time to time. One of the developments of civilization experienced by humans is internet technology. Along with the rapid development of internet technology, courier and logistics companies use the internet to survive in the midst of onslaught of competition between companies in the digital era. One of them is a State-Owned Enterprise (BUMN), PT. Pos Indonesia (Persero). Therefore, Pos Indonesia carries out various transformations to be able to compete with its competitors in order to survive in this digital era. Using theories and concepts of communication, public relations, public relations strategy and reputation. The method used in this research is a qualitative method with a case study approach. Collecting data using interviews, observations, and literature studies. The results of this study indicate that the PR strategy used is to implement four stages of PR, namely defining the problem, planning and programming, taking actions and communicating and evaluating. Then the communication is executed using the PESO model Keywords: Communication, Public Relations Strategy, Public Relations, Reputation. Abstrak. Peradaban manusia telah mengalami perjalanan yang sangat panjang seiring dengan berkembangnya kemampuan kognitif ras manusia dari masa ke masa. Salah satu perkembangan peradaban yang dialami oleh manusia adalah teknologi internet. Seiring dengan pesatnya perkembangan teknologi internet, perusahaan kurir dan logistik memanfaatkan internet agar tetap bisa bertahan di tengah gempuran persaingan antar perusahaan di era digital. Salah satunya adalah perusahaan Badan Usaha Milik Negara (BUMN) yakni PT. Pos Indonesia (Persero). Oleh karena itu, Pos Indonesia melakukan berbagai transformasi untuk bisa bersaing dengan para kompetitornya agar bisa tetap survive di era serba digital ini. Menggunakan teori dan konsep komunikasi, public relations, strategi public relations dan reputasi. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus. Pengumpulan data menggunakan wawancara, observasi, dan kajian Pustaka. Hasil dari penelitian ini menunjukkan strategi PR yang digunakan adalah mengimplementasi empat tahapan PR yakni defining the problem, planning and programming, taking actions and communicating serta evaluating. Kemudian komunikasi yang dijalankan menggunakan bauran PESO model. Kata kunci: Komunikasi, Public Relations, Strategi Public Relations, Reputasi.